Canopy-forming kelp forests persist in the dynamic subregion of the Broughton Archipelago, British Columbia, Canada - Man, L.; Barbosa, R. V.; Reshitnyk, L. Y.; Gendall, L.; Wachmann, A.; Dedeluk, N.; Kim, U.; Neufeld, C. J.; Costa, M. (Frontiers in Marine Science, 2025)
Canopy-forming kelp forests act as foundation species that provide a wide range of ecosystem services along temperate coastlines. With climate change, these ecosystems are experiencing changing environmental and biotic conditions; however, the kelp distribution and drivers of change in British Columbia remain largely unexplored. This research aimed to use satellite imagery and environmental data to investigate the spatiotemporal persistence and resilience of kelp forests in a dynamic subregion of cool ocean temperatures and high kelp abundance in the Broughton Archipelago, British Columbia. The specific objectives were to identify: 1) long-term (1984 to 2023) and short-term (2016 to 2023) kelp responses to environmental changes; and 2) spatial patterns of kelp persistence. The long-term time series was divided into three climate periods: 1984 to 1998, 1999 to 2014, and 2014 to 2023. The first transition between these periods represented a shift into cooler regional sea-surface temperatures and a negative Pacific Decadal Oscillation in 1999. The second transition represented a change into warmer temperatures (with more marine heatwaves and El Niño conditions) after 2014. In the long-term time series (1984 to 2023), which covered a site with Macrocystis pyrifera beds, kelp area increased slightly after the start of the second climate period in 1999. For the short-term time series (2016 to 2023), which focused on eight sites with Nereocystis luetkeana beds, most sites either did not change significantly or expanded in kelp area. This suggests that kelp areas remained persistent across these periods despite showing interannual variability. Thus, the dynamic subregion of the Broughton Archipelago may be a climate refuge for kelps, likely due to cool water temperatures that remain below both species’ upper thermal limits. Spatially, on a bed level, both species were more persistent in the center of the kelp beds, but across the subregion, Macrocystis had more persistent areas than Nereocystis, suggesting life history and/or other factors may be impacting these kelp beds differently. These findings demonstrate the spatiotemporal persistence of kelp forests in the dynamic subregion of the Broughton Archipelago, informing the management of kelp forest ecosystems by First Nations and local communities.